TYPES OF DIRECTIVE SPEECH ACTS FOUND IN THE SEA BEAST MOVIE SCRIPT - Kristina Dewi Sutriani; I.B. Gde Nova Winarta (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
Pragmatics is a branch of linguistics that studies the relationship between the context outside the language and the meaning of speech through interpretation of the situation in which it is spoken. There are many aspects of pragmatics; one of them is dealing with speech acts. Speech acts consist of many categories; one of them is directive speech act. This study aims to identify the directive speech act performed in “The Sea Beast” movie. Likewise, it will find out how often the directive speech act performed and which type of directive speech act that are most frequently used in the movie. This study used qualitative method in which data collection is done by watching the movie, analyzing the body movement and the dialogues of each character, and reading the script. A total of 50 directive speech acts were successfully identified. The result of analysis showed that the directive speech act of command is the most frequently used in the movie which had 15 data. The least frequently used directive speech act is warning which had 1 data. The study also revealed the importance of directive speech act in keeping the flow of storyline of the movie. This study is expected to give some useful insights in understanding what directive speech acts is. Keywords: pragmatics, directive speech act, The Sea Beast movie